METHODS FOR EVALUATING THE PERFORMANCE OF HETEROGENEOUS COMPUTER SYSTEMS - S. A. Sorokin; M. Z. Benenson; A. P. Sorokin (Российский технологический журнал)
Article is devoted to the performance evaluation of heterogeneous computing systems (platforms). The article substantiates the relevance of the use of problem-oriented configuration of computational systems for automated systems of information processing and management. The proposed mechanism is parallel and pipeline processing allowing to parallelize the task and thereby improve system performance. For interaction between modules it was proposed to use MPI-message passing interface between processes that perform a single task. The performance measurement was performed using recognized test kits Intel “MPI Benchmark” and “LINPACK HPL”, which allow to fully assess the effectiveness of the computing system and its relevance for the user. Given the graphics performance of the heterogeneous computing complex “profit center” in dealing with complex problems of linear algebra. The results obtained confirm high efficiency of MVP for various applications.